Contentious Minds How Talks and Ties Sustain Activism - Passy, Florence (Oxford University Press, 2020)
Why does the mind matter for joint action? Contentious Minds is a comparative study of how cognitive and relational processes allow activists to sustain their commitment. With survey data and narratives of activists engaged in three commitment communities, the minds of activists involved in contentious politics are compared with those devoted to institutional and volunteering action. The book's main argument is that activists of one commitment community have synchronized minds concerning the aim and means of their activism as they perceive common good (aim) and politics (means) through similar cognitive lenses. The book shows the importance of direct conversational contact with individuals in bringing about this synchronization. Assessing the synchronization within communities as well as the variation between them constitutes a major purpose of this book. It shows that activists construct and enact community-specific democratic cultures, thereby entering the public sphere through collective action. The book makes three major contributions. First, it emphasizes the necessity to return the study of the mind to research on activism, Second, it calls for an integrated relational perspective that rests on the structural, instrumental, and interpretative dimensions of social networks. Finally, it advocates a substantial integration of culture in the study of social movements by effectively valuing the role of culture in shaping a person's mind.